Ideologi Liberalisme Sebagai Konsep Dasar Keilmuan Pendidikan Islam - Khoirul Jazilah (Prodi PAI Fakultas Tarbiyah IAI Uluwiyah Mojokerto, 2022)
Liberalism ideology allows a person to achieve and decide his own future. If Islamic education fails to lead people to insan kamil, then the formulation of the problem in this study is how is the ideology of liberalism as the basic concept of Islamic education? The ideology of liberalism as a basic concept of Islamic education expects to make choices that are identified in line with Islamic education, so that the planned goals of Islamic education are achieved.